Developing user interface for network course based on experiential learning model / Sylvia Bangau - Bangau, Sylvia (2006)
Computer-based learning is one of the most popular methods nowadays to learn any kind of knowledge. User interface design plays an important role to an effective learning through computer-based. Poor design of the courseware was one of the main problems in computer-based learning. This may cause student felt lost, confused and did not achieve their learning objectives. This project was aim to design e-learning model based on Kolb's experiential learning model and to develop prototype for Communication network and protocol courseware based on the design model. Kolb's learning cycle consist of concrete experience, reflective observation, abstract conceptualization and active experimentation. Data was collected in order to match Kolb's experiential learning model functionality with network courseware. The project can help the user easier for learning and understanding the network course with the new approach of learning model. The project also provides a new approach in developing e-learning material. In future, we suggest that there should be more notes can be included in the courseware so that, it provide the student with the latest information regarding communication network and protocol subject.